La aplicación del juego cooperativo y su incidencia en el aprendizaje de los niños y niñas del ii nivel de educación inicial del centro educativo “Dirigentes del Futuro” de la parroquia Malacatos, cantón y provincia de Loja, periodo 2014-2015”. Lineamientos propositivos - Johanna Mercedes Sánchez Villa (2016)
This thesis refers: "THE IMPLEMENTATION OF COOPERATIVE GAME AND ITS IMPACT ON THE LEARNING OF CHILDREN OF PRESCHOOL EDUCATION LEVEL II Educational Center" leaders of tomorrow "THE Malacatos, canton and province of Loja PARISH, 2014 PERIOD -2015 ". Alternative guidelines. The main problem was how to impact the Implementation of Cooperative Learning Game children of Level II Early Childhood Education Center "Future Leaders" of the parish Malacatos Region and province of Loja, period 2014-2015? In this research the overall objective set was: To determine the incidence of cooperative games Learning children's initial level II Education School "future leaders" of the Malacatos, Canton and parish Province Loja, period 2014-2015”. Scientific, inductive, deductive, descriptive and statistical: To conduct the research the following methods were used. The techniques used were: The survey of teachers and the Test of Basic Functions applied to children's early education level II, to determine the level of learning of children. The field research was conducted with the participation of 51 children that corresponds to the Initial Level II parallel A and B, and 2 teachers of the School. A proposal for cooperative games is applied to improve the learning of children in preschool education, Level II Educational Center "Future Leaders" Malacatos parish, county and province of Loja, academic year 2014-2015. The representation of the results was conducted to analyze and interpret it was found that the teachers do not adequately use different cooperative games as game strategy, which directly affects the learning of children, causing difficulties therein. Therefore, it is recommended to teachers, having in mind that cooperative games, are essential for children's learning, enabling them to make their own meaningful learning and help them to propose and achieve specific goals in a relaxed, with a balanced, quiet and enjoyment attitude.